Measuring usability and children's enjoyment of a virtual toy in an imaginative play setting: a preliminary study - Mispa, Khairunnisa; Mansor, Evi Indriasari; Kamaruddin, Azrina; Hinds, Joanne (Little Lion Scientific, 2016)
This paper recounts a preliminary evaluation of children’s imaginative play whilst interacting with a virtual toy. Children aged 5-8 years old played with a virtual toy with a friend and their enjoyment and satisfaction of playing with the toy were evaluated. The complexity of social pretend play and the involvement of communicative strategies were taken into consideration to assist the inquiry of identifying the ability of the virtual toy to support children’s imaginative play. Our analysis demonstrated that children who managed to play imaginatively applied the social pretend play complexity and communicative strategies during the play session. The virtual toy supported children’s imaginative play, hence these findings can help to stimulate future research and the design of virtual toys to support play for remotely separated children.